Oedipal Inclinations In Jane Austen’s Character Emma Woodhouse: A Freudian Analysis - Asher Ashkar Gohar , Dr. Alam Zeb , Irfan Ullah Khan (Migration Letters, 2024)
This paper examines Jane Austen’s character ‘Emma Woodhouse’ in her novel Emma (published 1815), and argues that the titular character suffers from ‘Oedipus Complex’, which renders her emotions to abstain from romantic attachments or marriage throughout her youth. For this investigation, Sigmund Freud’s concept of Oedipus (‘Electra’, in case of women) Complex is employed which argues that if a girl’s unconscious desire for the opposite-sex parent remains unresolved, the ‘phallic-stage fixation’ arises, which therefore keeps her fixated on her father as her ‘libidinal object’. Freud says: “It is a distinct echo of this phase of development that the first serious love… of the girl [is] for an older man equipped with authority” (Freud 74). By utilizing this concept, this study contends that Emma Woodhouse subconsciously desires none other but her father as her ‘libidinal object’, which keeps her from loving or marrying anybody else. It is only through ‘repression’ of these desires into her unconscious, which springs forth from cultural bounds, that she chooses someone quite her elder, a father-figure, as her life partner in the conclusion of the novel.